Project Management for Information Technology (IT): Design of an anticipated IT project that would contribute to the achievement of the strategic goals of an organization - a case study of Water Resources Commission (WRC), Ghana - Kwadade-Cudjoe, Francis (Archives of Business Research, 2021)
Project management is the application of knowledge, skills, tools and techniques applied to project activities in order to roll out products / services to meet / exceed the needs and expectations of stakeholders. Project management has been popular within the Information Technology department of organizations for quite some time, and the approach for tackling the tasks involved is demanding. In that sense, getting the right and qualified human resource for handling such projects is one of the key success factors, for achieving results. Really dedicated and experienced IT professionals are scarce globally, and as the profession is also quite new to most people, there is a shortage of staff. In addition is the fear of not achieving objectives / goals if one ventures into it. However, with globalization being the norm currently, and multi-national organizations spreading / moving out to countries with less / cheaper labour costs, there is the need to get people to specialize in handling projects successfully. Executing IT projects successfully is the bane of most organizations, as the activities are technical and, in addition involve huge costs of expenditures.